Evaluation of Implementation of PSAK No. 71 the Provision for Impairment Losses (CKPN) at PT. Bank Rakyat Indonesia (PERSERO) KC Manado - Aksani Taqwiim; Inggriani Elim; Priscillia Weku (PT FORMOSA CENDEKIA GLOBAL, 2023)
CKPN is a number of funds formed to cover the risk of not being accepted back on financing channeled based on the procedures implemented by PT. Bank Rakyat Indonesia (Persero) KC Manado, which is a state-owned company, operates in community services such as providing credit to customers. The aim of this research is to evaluate the implementation of PSAK No. 71 regarding Allowance for Impairment Losses (CKPN) applied by PT. Bank Rakyat Indonesia (Persero) KC Manado by conducting research based on qualitative descriptive research methods and types. The results showed that Bank BRI KC Manado was calculated for CKPN using the ECL method which was forward looking in accordance with PSAK 71. The application of PSAK 71 increased the amount of Impairment Losses on loans thereby affecting the company's capital and additional costs incurred in preparing for the application of PSAK 71.